WORSHIP FACILITY IMPROVEMENT IN KELURAHAN SEI KERAH HILIR I KECAMATAN MEDAN PERJUANGAN, KOTA MEDAN - Lindarto, D; Harisdani, DD (Talenta Publisher, 2018)
Have been done community service activities such as the identification and provision of facilities requiring increased to accommodate Islamic religious activities, community involvement as a partner with which the Badan Kemakmuran Masjid (BKM) Serikat Amal Baik Mosque and SDIT Zahira school in Kelurahan Sei Kera Hilir I Kecamatan Medan Perjuangan, Kota Medan. Succession of transfer of energy-saving knowledge and training within the framework of Islamic spiritual education development in a sustainable manner. The concept of education link and match between the world of education with the implementation of direct education (practice) on the field is done in this activity by linking (linkage activity method) between SDIT educational activities by utilizing as part of religious practice is a real education. The result of this increase in worship facilities helped accommodate the nation's next generation of Islamic worship activities, SDIT Zahira students joined the surrounding community in an effort to promote the prosperity of Islam as well as preserving the architectural artifacts of the Amal Good Union mosque as the identity and landmark of Gang Sado, Medan.